2007
DOI: 10.1111/j.1365-2893.2007.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus E2 envelope protein induces dendritic cell maturation

Abstract: Maturation is a critical process for dendritic cells (DC) to gain or enhance their functions in antigen presentation and T-cell activation. In this study, we investigated the effect of hepatitis C virus (HCV) envelope protein E2 on DC maturation and related functions. We show that binding of E2 protein to DC leads to a change from immature to mature phenotype as detected by an increased expression of cell surface molecules including CD83, CD80, CD86, CD11c and MHC class II. The E2-matured DC showed higher capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…Consistent with this model is the prior finding that that HCV E2 increases MoDC CD80, CD83, CD86, CD40, and major histocompatibility complex II expression (57). However, in contrast to results obtained by Zhou et al (57) that E2-matured MoDCs showed a greater capacity to stimulate T-cell proliferation, IFN-␥ production, and IL-12 production, we found an impaired mDC capacity to activate naive T cells.…”
Section: Discussioncontrasting
confidence: 57%
“…Consistent with this model is the prior finding that that HCV E2 increases MoDC CD80, CD83, CD86, CD40, and major histocompatibility complex II expression (57). However, in contrast to results obtained by Zhou et al (57) that E2-matured MoDCs showed a greater capacity to stimulate T-cell proliferation, IFN-␥ production, and IL-12 production, we found an impaired mDC capacity to activate naive T cells.…”
Section: Discussioncontrasting
confidence: 57%
“…The inflammatory response is initiated by the presence of virus particles and subsequent infection of hepatocytes. Binding of microbial PAMPs, such as HCV glycoproteins, to antigen presenting cells results in activation and initiation of the inflammatory response and presentation of viral antigens to T cells [40,41,42,43,44,45]. Activation of these cells by viral proteins results in production of the soluble cytokines IL-1α, IL-1β and TNF-α, and the IL-6 family of cytokines, which in turn stimulate hepatocytes to produce acute‑phase proteins.…”
Section: Induction Of Acute Phase Proteins In Virus Infectionsmentioning
confidence: 99%
“…The HCV envelope glycoprotein E2 binding to DC was shown to lead to a shift from immature to mature phenotype through increased expression of cell surface molecules, such as CD83, CD80, CD11c, and MHC class II [142]. DCs that were E2-matured displayed a higher capacity to stimulate T cell proliferation and IFN-γ and IL-12 production in comparison to immature DCs.…”
Section: Hepatitis Viruses B and C And Dendritic Cellsmentioning
confidence: 99%
“…Moreover, E2-matured DCs showed a declined activity in endocytosis and phagocytosis upon maturation. Thus, the results indicate that E2 proteins not only induce DC maturation, but may also play a role in immune regulation during HCV infection [142]. Furthermore, DC migration appears to be significantly affected by interactions of HCV E2 with CD81 [128].…”
Section: Hepatitis Viruses B and C And Dendritic Cellsmentioning
confidence: 99%